Kodisas (komik digital sastra): transformasi cerita rakyat "Nyi Rambut Kasih" sebagai media pembelajaran sastra SMA - Naufalia, Afina; Fajrideani, Wulan; Alivia, Levri (Fakultas Sastra Universitas Negeri Malang, 2022)
Folklore is one of the literary teaching materials in high school which is usually often delivered through the lecture method. This can be boring to learners and incompatible with today's millennial generation. There needs to be innovation in literary learning, one of which is technology-based media in the form of transforming folklore into a digital comic. Digital comics can be used as a medium that is in accordance with technological developments and student interests, especially learning that is carried out online during this pandemic. Based on this, this study aims to transform the folklore "Nyi Rambut Kasih" into a Literary Digital Comic (KODISAS) as a medium for learning literature in high school. The transformed folklore is a folklore from Majalengka Regency, West Java "Nyi Rambut Kasih". The results of this study will be used as a medium for learning literature in high school. This research uses a descriptive qualitative research method, which describes the transformation of the folklore "Nyi Rambut Kasih" into a Literary Digital Comic (KODISAS) and its use as a literary learning medium in high school. From the results of the study, it shows that the transformation process underwent a reduction and addition of several aspects of the story. This is because in transforming the story usually refers to things that are more important and interesting to present. The aspects that are considered in transforming the story are aspects of content, characteristics, language, visualization, and cultural values. The results of this research are expected to be useful for the world of literary education and for the preservation of one of Indonesia's cultures.